Becoming physically active or maintaining physical activity during midlife is associated with biomarkers of amyloid‐beta, microglia, and temporal lobe integrity. (20th December 2022) - Akinci, Muge; Deulofeu, Carme; Palpatzis, Eleni; Peña‐Gomez, Cleofé; Fuentes‐Julian, Sherezade; Operto, Grégory; Garcia, Marina; Milà‐Alomà, Marta; Shekari, Mahnaz; Kollmorgen, Gwendlyn; Suridjan, Ivonne; Wild, Norbert; et al.
Abstract: Background: Physical activity (PA) has a beneficial effect on brain health in older age. Whether and how changes in PA during midlife are linked to brain health later in life remains understudied. In adults at risk for Alzheimer's disease (AD), we investigated the change in PA during midlife in relation to biomarkers of AD pathology, microglia, and brain integrity. Methods: A questionnaire investigating the minutes of PA per week was administered to 273 cognitively unimpaired participants at baseline and after a follow‐up of 4.1 (±0.8) years. The change in PA minutes/week between the two time points was calculated. Participants were classified in groups based on their activity levels at the two time points (active≥150 minutes, inactive<150 minutes): (1) maintained‐PA groups: active/active, inactive/inactive and (2) changing‐PA groups: inactive/active, active/inactive. During the follow‐up, participants had available CSF amyloid‐β42/40, phosphorylated‐tau and sTREM‐2 measured using either the exploratory Roche NeuroToolKit or the Elecsys ® immunoassays, amyloid PET, and structural MRI (AD signature [medial temporal lobe structures] thickness and hippocampal volume). We conducted multiple regression analyses with AD, microglia, and brain integrity biomarkers as outcome measurements and the change in PA minutes between the two time points as predictor, to assess dose‐dependent effects within the whole group, and maintained‐PA and changing‐PA groups separately. Furthermore, we investigated the associations of maintenance and change in activity status (PA groups) on the outcome measurements. All models were adjusted by age, sex, APOE‐ε4 status, education, and time interval between baseline and follow‐up. Results: The associations observed were group‐specific: increased minutes of PA was associated with greater AD signature thickness in the active/active group (p = 0.05) and greater hippocampal volume in the inactive/active group (p = 0.046). In the maintained‐PA groups, being active/active predicted higher CSF amyloid‐β42/40 (p = 0.024). In the changing‐PA groups, decreased minutes of PA predicted higher sTREM2 (p = 0.036) and brain amyloid‐β burden (p = 0.021). Additionally, the active/inactive group showed higher sTREM2 (p = 0.033) and brain amyloid‐β burden (p = 0.013). Conclusions: Our results suggest that becoming or staying physically active during midlife is associated with lower amyloidosis, microglia activation, and preserved temporal lobe integrity. The results further suggest a dose‐dependent effect of PA on brain health.